Rotating performance of Temcor joints for aluminum single-layer reticulated shells. (December 2021) - Yang, Lianping; Wang, Meng; Wei, Shen; Yu, Shaole
Abstract: The Temcor joints for the aluminum alloy single-layer reticulated shell has been widely used in the spatial structures due to simple fabrication method and construction convenience. The rotational performance of Temcor joints for the aluminum alloy single-layer reticulated shell has been experimentally investigated in this research. Four types of Temcor joints with various section heights were examined in this study. The failure mode, the moment-rotation curves and the stress distribution of the components and Gusset plates of Temcor joint were discussed. The results show that the failure was the section fracture caused by the weakened section of bolt holes in the lower flange of component end within the joint. The initial rotational stiffness of the joints was effectively improved by increasing their section heights. The maximum stress was observed at the outermost bolt, while the stress decreased with the distance from the center of gusset plate. This has thereby explained the failure of the joint region.